"Teacher, forgive me, I forgot to do it!" The impact of children's prospective memory on teachers' evaluation of academic performance. (7th August 2022) - Basso, Demis; Corradini, Giovanni; Cottini, Milvia
Abstract: Background: According to Munsat (1965, The concept of memory . University of Michigan), a person who makes frequent prospective memory (PM) errors is considered as having a flawed character rather than a bad memory. Given that PM completes its development only in young adulthood, this bias might occur not only within social relationships but also in school. However, little is known about the impact of this bias on academic performance. Aims: This study aimed to evaluate the impact of children's PM on teacher's evaluations of their academic performance (i.e., grades) and social skills. Sample: A total of 158 eight‐ and twelve‐year‐old children (48% females) participated in this study. Methods: A working memory (WM) updating task was used as ongoing task (OT), in which the PM task was embedded and required participants to respond whenever certain pictures appeared. Children's social skills were measured through teacher ratings, whereas grades were collected as indicators of teachers' assessment of academic performance. Children's WM span and inhibitory control were also assessed. Results: Results showed that 8‐ and 12‐year‐old children's academic performance was predicted by both PM performance and teachers' evaluations of social skills. However, social skills evaluations were not predicted by PM performance. WM span was related to grades in 8 year olds, while inhibitory control was related to PM performance in 12 year olds. Conclusions: These outcomes highlight that children's grades are not explained only by academic performance itself but also by other personal skills. Awareness of the biases which can occur when evaluating children's academic performance can help teachers to be more objective in their assessment.